Mekanisme Kepercayaan Jamaah Digital Terhadap Masjid Sejuta Pemuda - Kesthury Moh. Fikri; Ahmad Faiz Khudlari Thoha; Mauludi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study examines the influence of content authenticity on the digital congregation engagement of Masjid Sejuta Pemuda (MSP) through the mediating role of trust. Grounded in the Uses and Gratifications Theory and trust theory, this research employs a quantitative explanatory survey method involving 118 active Instagram followers of MSP. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results demonstrate that content authenticity significantly enhances trust (? = 0.815, p < 0.001) and engagement (? = 0.524, p < 0.001). Likewise, trust positively influences engagement (? = 0.434, p < 0.001) and partially mediates the effect of authenticity on engagement. These findings confirm that authentic religious content characterized by sincerity, consistency, and alignment with Islamic values strengthens digital trust and fosters active participation among followers. Theoretically, this research extends the Uses and Gratifications framework by integrating trust as a psychological bridge between media satisfaction and engagement. Practically, it underscores that authenticity is not a stylistic choice but an ethical necessity for sustaining meaningful digital da’wah interactions and institutional credibility.